(untitled) (Research, Society and Development, 2022)
Scientific and technological advances in the development of bone cements have been undergoing changes in order to obtain properties that are suitable for specific applications. The incorporation of other materials such as chitosan, collagen, oxides, polyethylene glycol, among others, which replace or even incorporate characteristics not present, are well explored, however, the influence of the processing of ceramic powders has been little studied. In this sense, the present work obtained the brushite/SrO/chitosan bone cement through the dissolution/precipitation method, using a mixture of wollastonite/strontium powder applied the methods of removing moisture by oven and desiccator. The samples were characterized through the analysis of curing and setting time, compressive strength, X-ray diffraction (XRD) and optical microscopy (OM). The results showed that the moisture removal method promotes variation of phases formed in the cements, as observed in the XRD, generating an improvement in the compressive strength. The temperature and time of the cements showed a reduction during their curing for the MPC samples. The microscopic analysis showed that the moisture removal method promoted greater porosity in the internal structure of the cement, which can provide an improvement in its compatibility with the applied bone region.